Moving toward genome-editing therapies for cardiovascular diseases - Kiran Musunuru (The Journal of Clinical Investigation, 2022)
The rapid invention of genome-editing technologies over the past decade, which has already been transformative for biomedical research, has raised the tantalizing prospect of an entirely new therapeutic modality. Whereas the treatment of chronic cardiovascular diseases has heretofore entailed the use of chronic therapies that typically must be taken repeatedly and frequently for the remainder of the lifetime, genome editing will enable the development of “one-and-done” therapies with durable effects. This Review summarizes the variety of available genome-editing approaches, including nuclease editing, base editing, epigenome editing, and prime editing; illustrates how these various approaches could be implemented as novel therapies for cardiovascular diseases; and outlines a path from technology development to preclinical studies to clinical trials. Although this Review focuses on PCSK9 as an instructive example of the various genome-editing approaches under active investigation, the lessons learned will be broadly applicable to the treatment of a variety of diseases.